2014
DOI: 10.1007/s00248-014-0491-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Healing Mud (Fango) from Roman Thermae Aquae Iasae Archaeological Site (Varaždinske Toplice, Croatia)

Abstract: We found well-preserved, rocky artefacts that had been buried in the healing mud (fango) for more than 1,500 years at the Roman archaeological site at Varaždinske Toplice. This Roman pool with fango sediments and artefacts is fed from hot sulphidic springs. The fango exhibited nearly neutral pH, a high level of organic C, an elevated concentration of heavy metals and a high total microbial biomass, greater than 10(8) cells per gram of dry weight. The dominant microbes, assessed by molecular profiling (denaturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Our data, along with those of other surveys of soil bacterial communities at archaeological sites using high-throughput sequencing techniques 6 , demonstrate that the taxonomic composition of soil bacterial communities concurs with that described as common in the soil environment 24 , 25 and evidence that bacterial diversity in these environments is not dominated by “rare” microbial taxa. However, archaeological sites have been described as potential sources of novel microbial species 5 , 9 . In the present study, OTUs affiliated to genus Pseudomonas were shown to be the most abundant ones and the main responsible for dissimilarity in soil bacterial community structure among the three layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data, along with those of other surveys of soil bacterial communities at archaeological sites using high-throughput sequencing techniques 6 , demonstrate that the taxonomic composition of soil bacterial communities concurs with that described as common in the soil environment 24 , 25 and evidence that bacterial diversity in these environments is not dominated by “rare” microbial taxa. However, archaeological sites have been described as potential sources of novel microbial species 5 , 9 . In the present study, OTUs affiliated to genus Pseudomonas were shown to be the most abundant ones and the main responsible for dissimilarity in soil bacterial community structure among the three layers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the presence of Pseudomonas in archaeological remains. In a culture-dependent study of the mud from a Roman thermae, strains classified as Pseudomonas were reported 9 . Xu, et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uhlik et al [23] isolated 54 cultured biphenyl-metabolizing bacteria from contaminated soil and obtained high concordance between MB and 16S rDNA analysis at the genus level only. Even if Mulec et al [47] did not compare MB identification with other methods, their work indicated that only 40% of the bacterial strains isolated from a thermal mud were identified by MB.…”
Section: Discussionmentioning
confidence: 99%
“…For example, on a geological scale, microbiological data can contribute to the understanding and reconstruction of past climatological, environmental, and sedimentary conditions. Moreover, on the time scales of human history and archaeology, microbiological data can contribute to unraveling human cultural habits, microbe-related human diseases, and alterations in cultural artifacts due to biochemical reactions [5]. For example, microbiological studies in archaeological contexts focused on pathogens and on the abundance of microbial spores or coprophilous microorganisms ([3] and references therein).…”
Section: Introductionmentioning
confidence: 99%